2000
DOI: 10.1002/1099-159x(200009/10)8:5<473::aid-pip337>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Surface passivation of crystalline silicon solar cells: a review

Abstract: In the 1980s, advances in the passivation of both cell surfaces led to the first crystalline silicon solar cells with conversion efficiencies above 20%. With today's industry trend towards thinner wafers and higher cell efficiency, the passivation of the front and rear surfaces is now also becoming vitally important for commercial silicon cells. This paper presents a review of the surface passivation methods used since the 1970s, both on laboratory‐type as well as industrial cells. Given the trend towards lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
224
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 630 publications
(243 citation statements)
references
References 33 publications
5
224
0
Order By: Relevance
“…In addition, we verified (on different type of wafers) that the passivation performance of the stack was similar to that obtained after "alnealing" (annealing the SiO 2 with a sacrificial Al-layer), which is known to lead to an excellent passivation quality. 18,34,35 It was, furthermore, found that annealing in N 2 led to the same passivation performance for the stacks as annealing in forming gas. The observation that the shape of the effective lifetime curves is the same for forming-gas annealed SiO 2 and SiO 2 /Al 2 O 3 stacks is in accordance with a similar prevailing mechanism underlying the passivation properties, i.e., a high level of chemical passivation.…”
Section: Resultsmentioning
confidence: 89%
“…In addition, we verified (on different type of wafers) that the passivation performance of the stack was similar to that obtained after "alnealing" (annealing the SiO 2 with a sacrificial Al-layer), which is known to lead to an excellent passivation quality. 18,34,35 It was, furthermore, found that annealing in N 2 led to the same passivation performance for the stacks as annealing in forming gas. The observation that the shape of the effective lifetime curves is the same for forming-gas annealed SiO 2 and SiO 2 /Al 2 O 3 stacks is in accordance with a similar prevailing mechanism underlying the passivation properties, i.e., a high level of chemical passivation.…”
Section: Resultsmentioning
confidence: 89%
“…It has been known for years that a-SiO:H exhibits visible photoluminescence [1][2][3] and has been applied in the p-i-n junction light-emitting diode [4]. In conventional c-Si solar cells, a-SiO:H has already been used as surface passivation layer [5]. Being a wide-optical-gap material it has important application as window layer in multi-junction solar cells [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The usual process to obtain antireflection and passivation coatings on p-type silicon solar cells is the growth of hydrogenated silicon nitride (SiN x :H) films by low pressure plasma-enhanced chemical vapor deposition (LP-PECVD) using silane (SiH 4 ) and ammoniac (NH 3 ) as gas precursors [3]. The major advantage of SiN x :H films is that they provide both an efficient front surface passivation and have an adequate antireflective behavior [4,5].…”
Section: Introductionmentioning
confidence: 99%